Perlawanan Terhadap Belenggu Patriarki pada Ketoprak Gaul Lakon Kalinyamat - Anggun Sila Falentina; Purnomo, Sucipto Hadi (JOM, 2024)
Traditional Javanese drama often portrays stories of political polemics and patriarchal leadership within the kingdom. Javanese culture typically places women in the shadow of men, relegating them to roles such as supporters who fulfill traditional functions of serving, adorning, and cooking. Traditional Javanese drama, including ketoprak, frequently narrates these themes. Ketoprak Gaul, through its play Kalinyamat as a primary source, positions women as central figures, necessitating examination to uncover codes of resistance against patriarchal constraints within Javanese cultural contexts. Through John Fiske's semiotic analysis, employing qualitative approaches and descriptive methods with data collection via observation and note-taking techniques, it is revealed that there are feminist values of (1) determined women, (2) confident women, (3) courageous women, and (4) strong women. Thus, the struggle for gender equality among women must begin with a desire, reinforced by conviction, and fortified with courage as a source of strength.